Pengaruh Karakteristik Pekerjaan, Pengembangan Karir Dan Kompensasi Terhadap Loyalitas Karyawan - Lumiu, Charlos Alexander; Pio, Riane J.; Tatimu, Ventje (Sam Ratulangi University, 2019)
This study aims to examine the effect of job characteristics, career development, and compensation on employee loyalty. The potential of existing human resources in the company must be utilized as well as possible, so as to be able to provide optimal output. An organization will run smoothly if all services provided by individuals to the organization get balanced attention and rewards. The general research objective is to examine and determine the effect of job characteristics, career development, and compensation on employee loyalty. The method used in this research is the quantitative descriptive method, using Structural Equation Modeling with Partial Least Square. The results obtained from the study that simultaneously the ability of the variable Job Characteristics, Career Development and Compensation in explaining the magnitude of the influence on the variable Employee Loyalty is 14%, the rest is explained by other variables outside this study.